Addition of Yeast Bread (Saccharomyces cerevisiae) in Feed to Increase Growth of Barramundi (Lates calcarifer) - Nunik Cokrowati; Ika Linda Hartati; Dewi Putri Lestari (Universitas Mataram, 2020)
Barramundi (Lates calcarifer) is known as Sea bass with a selling price of Rp.75,000 - Rp.80,000/Kg consumption size. The purpose of this study was to determine the effect of the addition of bread yeast with different doses to feed on the growth of Lates calcarifer. This study uses an experimental method with a Completely Randomized Design (CRD). The treatments were P0=0% yeast, P1=0.5%, P2=0.10%, P3=0.15%, P4=0.20% yeast from the weight of the feed given. The results of the study are the bread yeast influences the growth of Lates calcarifer. The highest absolute weight gain in P4 treatment was 0.507 g. The highest absolute length increase in P4 treatment was 0.990 cm. The lowest FCR at perlakuan P1 yaitu 15,55. The highest survival rates are P2, P3, and P4 which is 100%. Erythrocytes with the highest total amount in P4 treatment 12,58x106 - 18,62x106 cells/mm3. Leukocytes with the highest total number in P2 treatment were 27,96x106 - 44,641x106 cells/mm3. Water quality parameter values in the maintenance media are in the range of requirements for Lates calcarifer cultivation. The conclusion of the study is the addition of bread yeast affects the growth of Lates calcarifer and the optimal dose that can increase the growth is 0,20%.